Long‐term risk of heart failure and other adverse cardiovascular outcomes in primary Sjögren's syndrome. (11th December 2022) - Sun, Guoli; Fosbøl, Emil L.; Yafasova, Adelina; Faurschou, Mikkel; Lindhardsen, Jesper; Torp‐Pedersen, Christian; Køber, Lars; Butt, Jawad H.
Abstract: Background: Data on long‐term cardiovascular outcomes in primary Sjögren's syndrome (PSS) are scarce. Objectives: We aim to investigate the long‐term rate of incident heart failure (HF) and other adverse cardiovascular endpoints in patients with PSS compared with the general population and to investigate mortality in individuals with incident HF with or without a history of PSS. Methods: Using Danish nationwide registries, PSS patients (diagnosed 1996–2018) without a history of other autoimmune diseases were each matched with four individuals from the general population by sex, age, and comorbidities. Multivariable Cox regression was used to estimate the rate of cardiovascular outcomes. In addition, the rate of death from any cause was compared between PSS patients with incident HF and four age‐ and sex‐matched HF patients without PSS. Results: In total, 5092 patients with newly diagnosed PSS were matched with 20, 368 individuals from the general population (median age 57 years, 87.3% women, median follow‐up 7.4 years). The cumulative incidence of HF at 10 years was 4.0% for PSS patients and 2.8% for matched individuals. After adjustment, patients with PSS had a higher associated rate of incident HF (hazard ratios [HR] 1.42 [95% CI, 1.20–1.68]) and other cardiovascular outcomes, compared with the background population. PSS patients with incident HF had a similar rate of death from all‐cause mortality compared with HF patients without PSS (HR 0.94 [0.74–1.19]). Conclusions: Patients with PSS had a higher associated rate of incident HF and other cardiovascular outcomes compared with the general population. In individuals with incident HF, a history of PSS was not associated with increased mortality. Abstract :